Managing an alternative social financing for entrepreneurs - Ahmad Kamely, Aimadhuddin; Khaliq, Ahmad; Mohd. Nor, Rizal (2019)
Crowdfunding is developing in popularity as a new form of both investment opportunities and source of raising capital. This needs to be studied. The aim of this paper is to explore and expand the understanding of the newly invented crowdfunding, types of the existing platforms of the industry. We studied unsearched area of crowdfunding platforms that are registered in securities commission Malaysia and Kapitalboost platform of Singapore and their mode of investment. The paper uses case study method of six platforms of crowdfunding. Authors also looked in depth and reviewed a current literature on crowdfunding. It established an investment model of crowdfunding that will be suitable for the Muslim investors and anyone who is looking into an ethical investment that will contribute to the wellbeing of the societies as whole through Mudharabah and Musharakah investment. We mainly focused in Malaysia as we wanted to investigate the efficiency of these platforms how the entrepreneurs and small business can grow without falling into the trouble of the traditional banks higher cost and debt problems. The findings explored that equity crowdfunding could bring more benefit and less harm to entrepreneurs however none of the models used by the six registered crowdfunding platforms of Malaysia is Islamic type of investment. The paper therefore proposes two types of models that is based on equity-in and equity-out as we found that this is the best model to help investor invest in the project and dissociate debt from entrepreneur. The research contribution is given as the equity crowdfunding over the debt based through Islamic investment method of investing (Musharakah and Mudharabah) is better.